Quality of life in Ecuadorian patients with established rheumatoid arthritis - Intriago, Maria (Open Access Rheumatol, 2019)
PURPOSE: To evaluate quality of life in patients with established rheumatoid arthritis (RA) and identify the factors that negatively affect it. METHODS: This was a cross-sectional study with patients with established RA from a rheumatology center in Ecuador. The RA Quality of Life (RAQoL) questionnaire was used to assess QoL and the Health Assessment Questionnaire — disability index (HAQ-DI) questionnaire for functional capacity. In addition, demographics, clinical characteristics, and markers of disease activity were included. Data were analyzed using SPSS 22. RESULTS: Of 186 patients, 89.8% were women, with a mean age of 51 years, 86.6% had symmetrical polyarticular involvement, 40.3% erosions, 46.8% morning stiffness, 46.8% xerophthalmia, and 39.2% fatigue. Depression was the most frequent comorbidity — 42.5%. The mean HAQ-DI score was 0.8, and 26.9% had functional disability. The mean RAQoL score was 7.2. Xerophthalmia, xerostomia, fatigue, morning stiffness, and depression were related to higher scores in the RAQoL (p<0.05). The mean RAQoL was higher in patients with more disease activity and comorbidities (p<0.05). Likewise, patients with functional disability had a mean RAQoL score of 15.6 versus 4.1 in patients without disability (p<0.05). There were positive correlations between RAQoL and ESR, CRP, painful-joint count, swollen-joint count, VAS of pain, and physician assessment (p<0.05). CONCLUSION: QoL is severely affected in patients with RA. Depression, fatigue, morning stiffness, pain, high disease activity, and disability have a negative effect on QoL in RA. Likewise, patients with more comorbidities and extraarticular manifestations show worse QoL.